Kingdom of the Netherlands-Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper highlights that over the past decade, the Netherlands has undergone a remarkable fiscal adjustment, with the deficit, the tax burden, and the expenditure-to-GDP ratio falling significantly. The switch from a deficit-target-based to an expenditure-target-based fiscal framework in 1994 and commitments to two successive four-year fiscal plans have played an important role. The current multiyear framework expires in 2002, and the Study Group on the Budgetary Margin has produced recommendations for the coming government period.